Calcificaciones heterotópicas en paciente politraumatizado - Trasante Borches, María Soledad; Giovenco, Marcela B.; Bernard, Nicolás E.; Diehl, María; Zanotti, Gerardo; Russo, Paula; Andresik, Diego (Revista del Hospital Italiano de Buenos Aires, 2017)
-